Luminescence enhancement of OLED lighting panels using a microlens array film. Issue 4 (2nd October 2018) - Han, Jun-Han; Moon, Jaehyun; Cho, Doo-Hee; Shin, Jin-Wook; Chu, Hye Yong; Lee, Jeong-Ik; Cho, Nam Sung; Lee, Jonghee
ABSTRACT: The enhancement of the luminance of organic light-emitting diode (OLED) panels with various areas (2.25–6084 mm 2 ) using a microlens array (MLA) film was investigated. The luminance enhancement was dependent on the viewing angle, and the largest enhancement (64%) was observed in the normal direction while 60 and 18% enhancements were observed at 60 and 30°, which led to lower enhancement (38%) of the total luminous flux compared with the luminance enhancement (64%) in the normal direction. The luminance enhancement with the MLA film also depended on the panel area, and the smaller panels showed lower luminance enhancement than the larger ones. As for the small panels, the straying light beyond the panel areas significantly affected the luminance of the panels, and over 60% luminance enhancement was observed in the normal direction for the large panels (2500 and 6084 mm 2 ) with the MLA film while only 48 and 58% luminance enhancements were observed at the small panels (2.25 and 70 mm 2 ).